Heavy Metals Pollution in Drinking Water Sources: A Case Study from Kulim Hi-Tech Park, Malaysia - Muhamad Radzi Zainon; Mohd Yusmaidie Aziz; Ahmad Razali Ishak; Muhamad Azwat Abdullah; Abdul Rohim Tualeka; Rafeezul Mohamed; Hisham Atan Edinur; Siti Aisyah Mualif; Muhammad Azrul Zabidi; Maisarah Nasution Waras (Jurnal Kesehatan Lingkungan)
Introduction: Heavy metal content within drinking water poses significant risks to health and the environment. Given industrial impact on Kulim’s water quality, this study determined the concentrations of iron (Fe), manganese (Mn), zinc (Zn), cadmium (Cd), and nickel (Ni) in various water sources around Kulim Hi-Tech Park (KHTP) and assess associated with chronic heath risks. Methods: We measured these five heavy metals in 30 water samples from tap water, rivers, and ponds, within and around Kulim Hi-Tech Park (KHTP), using Atomic Absorption Spectroscopy. Non-carcinogenic risk was assessed by calculating Hazard Quotient (HQ) and Hazard Index (HI), while carcinogenic risk used Excess Lifetime Cancer Risk (ELCR). Results and Discussion: Mean concentrations averaged between 0.0177 ± 0.0017 mg/L and 0.8652 ± 0.0606 mg/L; nickel showed the highest mean, followed by iron, zinc, manganese, and cadmium. Notably, concentrations of nickel, and in some instances iron and cadmium, exceeded regulatory limits. HQ and HI suggested no immediate adverse health effects from exposure to iron, manganese, and zinc. However, ELCR values for cadmium and nickel surpassed acceptable levels, indicating potential carcinogenic risks from long-term exposure. It is important to note that risk assessment for iron, manganese, and zinc is based on mean concentrations that include proportion of samples below the Limit of Quantification (LOQ), warranting cautious interpretation. Conclusion: This study provides crucial baseline data on heavy metals in KHTP water resources, underscores more investigation and potential remediation strategies to safeguard public and environmental health.